Social Impact Measurement by Social Return on Investment Based on Islamic Social Enterprise - Fransiska, Ina Berliana; Manoarfa, Hilda; Juliana, Juliana; Asih, Vemy Suci (PT. Student Rihlah Indonesia, 2025)
This research is motivated by socio-economic imbalance that cannot be handled properly by the government so that the presence of social enterprise is needed in the midst of society. Evaluation and sustainable development in social enterprise is necessary to maintain its existence, by measuring the social impact that results from the social mission business. The concept of social enterprise itself is generally neutral without being based on religious values. The emergence of the concept of Islamic social enterprise is a novelty. This study uses a qualitative descriptive method that aims to describe the actual conditions of the application of the Islamic social enterprise concept in a company and measure their social impact. With injection of Islamic social enterprise in the process of measurement, this research has added value than others. The subject is Catenzo shoe company located in Cibaduyut, Bandung City. Catenzo has a significant role in empowering local shoe craftsmen in that area. The population is Catenzo partner shoe craftsmen as the main recipient of the impact of empowerment, amounting to 121 people with 25 people as sample. The Social Return on Investment (SROI) method is a measuring tool used in this study. The SROI ratio calculation results show that the Catenzo shoe company succeeded in creating a social impact or benefit for the partner shoe craftsmen.